Impulsivity in Parkinson's disease is associated with altered subthalamic but not globus pallidus internus activity. Issue 11 (19th August 2017) - Rossi, Peter Justin; Shute, Jonathan B; Opri, Enrico; Molina, Rene; Peden, Corinna; Castellanos, Oscar; Foote, Kelly D; Gunduz, Aysegul; Okun, Michael S
Abstract : Background: A significant subset of patients with Parkinson's disease (PD) suffer from impulse control disorders (ICDs). A hallmark feature of many ICDs is the pursuit of rewarding behaviours despite negative consequences. Recent evidence implicates the subthalamic nucleus (STN) and globus pallidus internus (GPi) in reward and punishment processing, and deep brain stimulation (DBS) of these structures has been associated with changes in ICD symptoms. Methods: We tested the hypothesis that in patients with PD diagnosed with ICD, neurons in the STN and GPi would be more responsive to reward-related stimuli and less responsive to loss-related stimuli. We studied a cohort of 43 patients with PD (12 with an ICD and 31 without) undergoing DBS electrode placement surgery. Patients performed a behavioural task in which their action choices were motivated by the potential for either a monetary reward or a monetary loss. During task performance, the activity of individual neurons was recorded in either the STN (n=100) or the GPi (n=100). Results: The presence of an ICD was associated with significantly greater proportions of reward responsive neurons (p<0.01) and significantly lower proportions of loss responsive neurons (p<0.05) in the STN, but not in the GPi. Conclusions: These findings provide further evidence of STN involvement in impulsive behaviour in the PD population.